Cascading failure model in power grids using the complex network theory. Issue 15 (1st November 2016) - Wenli, Fan; Zhigang, Liu; Ping, Hu; Shengwei, Mei
Abstract : The massive power flow transferring triggers the node overload cascade, which further activates the protection system hidden failures. In this study, we propose a cascading failure model based on complex network theory by combining the node overload failures and hidden failures of transmission lines in blackouts together. The model concerns the electrical characteristics, which has not been involved in the existed cascading failure model when modelling node loads. The cascading failure simulations on the 500 kV Center China power grid and the IEEE‐300‐bus test system demonstrate that the proposed cascading failure model with node load built on electrical characteristics can bring better network invulnerability than the model with that constructed on pure structure topology. Meanwhile, the proposed model can better exhibit the negative aspects of hidden failures in the blackouts. The deliberate attacks based on high‐risk nodes can decrease the invulnerability of power grids more seriously compared with those based on high‐degree and high‐load nodes. The results provide a new way to analyse the power grid cascading failure mechanism based on the complex network theory.